A Review of Augmented Reality Applications in Civil Infrastructure During the 4th Industrial Revolution - Xu, Jiaqi; Moreu, Fernando (Frontiers in Built Environment, 2021)
The 4th industrial revolution started in 2016 and referred to a new phase in the Industrial Revolution. One of the most significant technological evolvement during the 4th industrial revolution is Augmented Reality (AR) technology. AR superimposes interactional virtual objects/images to real environments. Because of the interaction and see-through characteristics, AR is better applied to engineering than Virtual Reality (VR). The application of AR in civil infrastructure can avoid artificial mistakes, improve efficiency, and saves budget. This paper reviews AR applications in civil infrastructure, focusing on research studies in the latest five years (2016-2020) and their milestone developments. More than half of the AR research and implementation studies have focused on the last five years' construction domain. Researchers deploy AR technologies in onsite construction to assist in discrepancy checking, collaborative communication, and safety checking. AR also uses building information models (BIM) to produce detailed 3D structural information for visualization. Additionally, AR has been studied for structural health monitoring (SHM), routine and damage detection, energy performance assessment, crack inspection, excavation, and underground utility maintenance. Finally, AR has also been applied for architecture design, city plan, and disaster prediction as an essential part of smart city service. This paper discusses the challenges of AR implementation in civil infrastructure and recommends future applications.